Tuning of aggregation and film self-assembly of monomethincyanine dyes through variation of their monomer structure - Sieryk, M.M.; Dimitriev, O.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2019)
Formation of condensed films and solution aggregates of four different monomethincyanine dyes has been studied using optical absorption spectroscopy and simulation methods, depending on variation of the dye monomer structure. The structure of the molecular dimer as a basic unit for the formation of the condensed state was found to be largely dependent on heteroatoms in the dye structure and the presence of end hydrocarbon groups. The above factors mainly determine the mutual position of molecules in the dimer. It has been found that mutual orientation, intermolecular distance, and overlap of the adjacent molecules are the major factors influencing absorption spectra of dye aggregates. The dimer geometry that plays the primary role in film nucleation, however, has been shown to undergo changes depending on the temperature conditions or film thickness.